2017
DOI: 10.1111/ijd.13697
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of human papillomavirus infection in the development of lichen sclerosus

Abstract: Lichen sclerosus (LS) is a chronic inflammatory skin disease of unknown origin predominantly affecting the anogenital area that causes pruritus and pain and is associated with an increased risk of malignancy. In some cases, LS vanishes after application of imiquimod, raising the question whether human papillomavirus (HPV) may have an etiopathogenic role in anogenital LS. The databases MEDLINE and Embase were systematically searched using the PRISMA guidelines. Twenty-seven papers were included that reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
3
26
1
1
Order By: Relevance
“…HPV infection has been implicated as a causative agent of genital LS (1,6). The median prevalence of HPV in genital LS is 22% (6). One could expect a much higher prevalence of HPV in genital LS because the lifetime prevalence of HPV is high (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV infection has been implicated as a causative agent of genital LS (1,6). The median prevalence of HPV in genital LS is 22% (6). One could expect a much higher prevalence of HPV in genital LS because the lifetime prevalence of HPV is high (4).…”
Section: Discussionmentioning
confidence: 99%
“…One could expect a much higher prevalence of HPV in genital LS because the lifetime prevalence of HPV is high (4). There are some facts that contradict the association of genital LS and HPV as a causative agent, such as the fact that genital LS is never seen in sexual partners; moreover, despite widespread immunization against HPV, there is no decline in the genital LS incidence, and so it can be concluded that there is a lack of clinical correlation of LS with HPV infection (6)(7)(8). Von Krogh et al found that 32% of men afflicted with LS revealed a positive history of penile warts (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent systematic search of 27 papers reporting the prevalence of HPV in LS identified that HPV was present in 22% of LS cases. It also highlighted HPV 16 as the most common genotype …”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…It also highlighted HPV 16 as the most common genotype. 21 There is also growing evidence for a possible autoimmune cause. In vulvar LS lesions, Farrell et al 22 demonstrated increased levels of interferon gamma, tumor necrosis factor, and interleukin-1.…”
Section: Indicated That Bxomentioning
confidence: 99%